Beyond localism: The micropolitics of local legitimacy in a community-based organization. (February 2017) - Molden, Olivia; Abrams, Jesse; Davis, Emily Jane; Moseley, Cassandra
Abstract: Abstract Place-based non-governmental organizations have assumed expanded roles in the processes of community development and environmental governance. However, to date there has been insufficient attention paid to the processes by which these organizations establish the necessary legitimacy among local populations and community leaders to be able to act and speak on behalf of the community. This paper draws on a case study of the community forestry efforts of one community-based organization in the rural US West to analyze how the organization developed and maintained local legitimacy. Our analysis of the micropolitics of community-based social and environmental governance highlights three interrelated resources that contributed to local legitimacy: interpersonal relationships, shared development narratives, and achievement of demonstrable practical outcomes. At the same time, we find important constraints to achieving outcomes, and therefore to increasing local legitimacy, that are reflective of larger structural constraints in the context of neoliberal governance. We argue for greater consideration of the quotidian and embodied interactions of individuals working in particular places—as influenced by their larger structural contexts—to understand the dynamics of small place-based organizations. Highlights: Local legitimacy is key to the success of place-based NGOs. Personal relationships can serve as one component of local legitimacy. Legitimacy is bolstered by engagement with dominant local narratives. Demonstrating practical outcomes generates additional legitimacy. Structural constraints place limits on the effectiveness of local action.